Determining stoichiometry and kinetics of two thermophilic nitrifying communities as a crucial step in the development of thermophilic nitrogen removal. (1st June 2019) - Vandekerckhove, Tom G.L.; Kerckhof, Frederiek-Maarten; De Mulder, Chaïm; Vlaeminck, Siegfried E.; Boon, Nico
Abstract: Nitrification and denitrification, the key biological processes for thermophilic nitrogen removal, have separately been established in bioreactors at 50 °C. A well-characterized set of kinetic parameters is essential to integrate these processes while safeguarding the autotrophs performing nitrification. Knowledge on thermophilic nitrifying kinetics is restricted to isolated or highly enriched batch cultures, which do not represent bioreactor conditions. This study characterized the stoichiometry and kinetics of two thermophilic (50 °C) nitrifying communities. The most abundant ammonia oxidizing archaea (AOA) were related to the Nitrososphaera genus, clustering relatively far from known species Nitrososphaera gargensis (95.5% 16S rRNA gene sequence identity). The most abundant nitrite oxidizing bacteria (NOB) were related to Nitrospira calida (97% 16S rRNA gene sequence identity). The nitrification biomass yield was 0.20–0.24 g VSS g −1 N, resulting mainly from a high AOA yield (0.16–0.20 g VSS g −1 N), which was reflected in a high AOA abundance in the community (57–76%) compared to NOB (5–11%). Batch-wise determination of decay rates (AOA: 0.23–0.29 d −1 ; NOB: 0.32–0.43 d −1 ) rendered an overestimation compared to in situ estimations of overall decay rate (0.026–0.078 d −1 ). Possibly, the inactivation rate rather than the actual decay rate was determined in batch experiments. Maximum growth rates of AOA and NOB were 0.12–0.15 d −1 and 0.13–0.33 d −1 respectively. NOB were susceptible to nitrite, opening up opportunities for shortcut nitrogen removal. However, NOB had a similar growth rate and oxygen affinity (0.15–0.55 mg O2 L −1 ) as AOA and were resilient towards free ammonia (IC50  > 16 mg NH3 -N L −1 ). This might complicate NOB outselection using common practices to establish shortcut nitrogen removal (SRT control; aeration control; free ammonia shocks). Overall, the obtained insights can assist in integrating thermophilic conversions and facilitate single-sludge nitrification/denitrification. Graphical abstract: Image 1 Highlights: Thermophilic nitrification yield was high, resulting mainly from a high AOA yield. AOA belonged to the Nitrososphaera genus, NOB to Nitrospira calida . Batch-wise determined decay rates were overestimated compared to in situ estimation. NOB kinetics and high FA tolerance might complicate thermophilic NOB outselection. Higher maximum temperature for AOA activity retention (55 °C) vs NOB (50 °C).